Peran Komitmen Organisasi, Perspektif Budaya Tri Hita Karana, dan Whistleblowing System dalam Pencegahan Fraud - Made Wina Sanjani; Desak Nyoman Sri Werastuti (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
Thissresearch aims to analyzezthe influencerof organizational comitment, cultural perspective of tri hita karana and whistleblowing system on fraud prevention. This study uses primary or quantitative data from questionnaireddataousingka likertfscale. This researchswass conductedi at BPKAD Karangasem Regency. The population in this study wereiallaemployeessin theeReporting and Billing Field at BPKAD Karangasem Regency as many as 98 people. Theysamplingsmethod used in this study is the total sampling method, so that the number of samples is equalttoia populationtof 98 respondents. Therdatavof this study were collectedwusing a questionnairedwhichfwas then processed byymultipleylinear regressionfanalysis with the help of SPSSsversione22. The resultssshowed that organizational commitment, cultural perspective of tri hita karana and whistleblowingfsystemihad a positivefeffectqon fraudiprevention